FACTORS OF INFLUENCE ON PREPAREDNESS OF THE PRIVATE SECURITY MEMBERS FOR FIRE EMERGENCIES - Cvetković, Vladimir; Pavlović, Slavica; Janković, Bojan D. (NBP. Nauka, bezbednost, policija, 2021)
The subject of the research is examination of the factors of influence on the preparedness of members of the private security to react in case of fires. In addition to determining the preparedness index, there are deeper insights into the interrelationships between various selected variables and the level of preparedness of members of the private security. Using the random sampling method, 300 adult members of the private security were selected, and they participated in the research. The results of the research indicate that members of the private security are not sufficiently prepared to react to fires. Starting from the fact that the role of members of the private security in disaster conditions is rather poorly and insufficiently researched phenomenon. The research results can be used as a starting point for conducting further research in this area.